2021
DOI: 10.31235/osf.io/qwxz3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baby Bust: Falling Fertility in US Counties Is Associated with COVID-19 Prevalence and Mobility Reductions

Abstract: The United States experienced a 3.8 percent decline in births for 2020 compared with 2019, but the rate of decline was much faster at the end of the year (8 percent in December), suggesting dramatic early effects of the COVID-19 pandemic, which began affecting social life in late March 2020. Using birth data from Florida and Ohio counties through February 2021, this analysis examines whether and how much falling birth rates were associated with local pandemic conditions, specifically infection rates and reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 11 publications
5
25
0
2
Order By: Relevance
“…Today, newly released vital registration statistics allow for early empirical assessments of these claims. In the United States, a 3.8% drop in births was computed for 2020 compared to 2019, with an accelerating rate of decline at the end of 2020 ( 14 ). Across a set of 17 countries, Sobotka et al ( 15 ) find that the rate of decline in births increased, on average, from 5.1% in November 2020 to 8.9% in January 2021, when compared with the same month of the previous year.…”
mentioning
confidence: 99%
“…Today, newly released vital registration statistics allow for early empirical assessments of these claims. In the United States, a 3.8% drop in births was computed for 2020 compared to 2019, with an accelerating rate of decline at the end of 2020 ( 14 ). Across a set of 17 countries, Sobotka et al ( 15 ) find that the rate of decline in births increased, on average, from 5.1% in November 2020 to 8.9% in January 2021, when compared with the same month of the previous year.…”
mentioning
confidence: 99%
“…However, in other European countries such as Denmark, Finland, the Netherlands, and Norway, no changes to previous trends in monthly birth rates were observed for December 2020 and January 2021 (Sobotka et al, 2021). Evidence at the county-level for the USA shows an overall annual decline in births in 2020 of 3.8%, where reductions in births were observed throughout the country, and steeper declines were detected in counties with higher prevalence of COVID-19 infections and in counties where mobility diminished the most (Cohen, 2021).…”
Section: Observed Effects Of Covid-19 On Fertilitymentioning
confidence: 87%
“…A wide interest on the consequences of the COVID-19 emergency on fertility has arisen worldwide in the scientific community since the beginning of the pandemic. Prediction about drops in births have been largely shared in the demographers' community (e.g., Lappegard et al 2020, Lindberg et al 2020, Micelli et al 2020, Ullah et al 2020, Wilde et al 2020) and preliminary data from birth statistics confirm a drop in the birth rates 8-9 months after the beginning of the health emergency in Italy (Blangiardo 2021), as well as in the US and several other European and Asian countries (Cohen 2021;Sobotka et al 2021). In Italy, the very low fertility level was already a concern for demographers and policy makers before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Against the previous discussion on the role of economic uncertainty during recessions and on the Italian context, a reduction in fertility can be expected. Studies on Italy and on other developed countries have already shown some evidence of that (Cohen 2021, Li et al 2021Lindeberg et al 2020, Guetto et al 2020, Micelli et al 2020, Blangiardo 2021, while studies on low and medium-income countries (Emery andKoops 2021, Zhu et al 2020) found mixed effects of the pandemic on fertility intentions. In Italy, first data released by ISTAT 8 shows that, compared to the same months of the previous year, in December 2020 the number of births declined by 10.3%; this is the first month in which the effects of the first epidemic wave are observable.…”
Section: The Impact Of the Covid-19 Pandemic On Births And Fertility Intentionsmentioning
confidence: 98%
See 1 more Smart Citation